Komunikasi Nonverbal Dalam Strategi Marketing Lowbudget Red Bull - Sepriadi Saputra; Fera Indasari (UNIVED PRESS, Universitas Dehasen Bengkulu, 2022)
Red Bull is an Austrian company originating from Karting Deng in Thailand that sells energy drinks with the same name as one of the world's most famous energy drink brands, which at first did not sell well in marketing and decided on a unique and cost-effective idea.The low-budget marketing strategy carried out by Red Bull is in the form of disposing of product cans in the trash or in crowded places. So that consumers will think that the product is selling well in the market, with this Red Bull getting brand awareness with a low cast strategy. It can be seen by what Red Bull does, it can be proven that a unique and odd-looking idea can also attract consumers. This phenomenon can occur through non-verbal messages given by the Red Bull marketing team to individuals who pass their marketing goals such as the characteristics of symbolic interaction, namely someone will interpret the sign or symbol that has been given to them by others, here the people interpret the sign given as the success of a product which means the possibility of the product has good quality and is worth trying. In this article, the author uses a qualitative method which is a method that focuses on in-depth observations. Therefore, the use of qualitative methods in research can result in a more comprehensive study of a phenomenon with a literature study approach where data and information that support writing are collected by conducting library searches, searching for relevant sources related to the discussion material carried out.